2001
DOI: 10.1103/physreva.63.053407
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic blueshift of high-order harmonics from Ar and Ne atoms in an intense femtosecond laser field

Abstract: A strong blueshift of high-order harmonics was observed when intense femtosecond Ti:sapphire laser pulses were applied to Ar and Ne. The blueshift was systematically investigated for various experimental parameters, such as laser intensity, laser-pulse duration, and gas density. We observed the harmonic blueshifts of two times the laser frequency in the 39th harmonic from Ar and four times the laser frequency in the 85th harmonic from Ne. A semiclassical calculation predicted the inverse proportionality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…This imbalance of HHG will lead to a net blue shift in HHG. This has been experimentally confirmed in [12,19]. (5)).…”
Section: Nonadiabatic Blue Shift In Hhgsupporting
confidence: 56%
“…This imbalance of HHG will lead to a net blue shift in HHG. This has been experimentally confirmed in [12,19]. (5)).…”
Section: Nonadiabatic Blue Shift In Hhgsupporting
confidence: 56%
“…This is indeed the case in our measurements and is consistent with our observation that the relative shift increases with the order. This agrees with the earlier results from [25], where a non-adiabatic blue-shift is reported as well. It can be concluded that the total observed harmonic blue-shift obtained is due to both ionization (adiabatic) and non-adiabatic effects.…”
Section: Resultssupporting
confidence: 93%
“…3 and 4, we clearly observe a shift of the high-harmonic output wavelengths as a function of pressure and drive laser chirp. In comparison with the observations of others [15,25] 2 and P = 40 mbar), the blue-shift may result from three mechanisms. One of the mechanisms is an ionization induced blue-shift of the drive laser.…”
Section: Resultsmentioning
confidence: 40%
See 1 more Smart Citation
“…Harmonics were generated on the leading edge of the laser pulse, which also experienced self-phase modulation and blue-shifting due to ionization of the gas. Thus, they can shift in energy slightly during the high harmonic generation process (28,29) and must be independently measured. In this work, the energy of 7ω was determined from the photoelectron spectra of known compounds (acetone and methyl azide), while 5ω was measured on a home-built spectrometer.…”
Section: Experimental Methodsmentioning
confidence: 99%